Rohingya Crisis: a Possible Threat to the Character Strengths of Indians - Chaube, Nandita; ., . (International Journal of Engineering and Technology, 2018)
The current study focuses on the influence of Rohingya crisis on the character strengths of Indian citizens. The study explains about the Rohingya crisis and its origination. It is discussed in the study that how chaotic conditions in Myanmar resulted in the exodus of Rohigya muslims from the country who are infiltrating neighbouring countries which are best approachable to them. Countries which are the signatories of UNHCR are supposed to allow them to enter their country but India not being a signatory of the same should not be forced to do that. However, the debate is still continuing on this issue referring few acts which support the permission to refugees to enter our country. In such circumstances Rohingyas are struggling for their livelihood and survival and getting involved in many antinational and anti-social activities. Consequently the legal citizens of India are substantially suffering and facing threat to develop their character strengths. The circumstances specially affecting the character strengths of   forgiveness, social intelligence, kindness, humour, love and modesty etc. because their main focus is on the fulfilment of their daily necessities, based on the resources and peaceful social environment which is getting disturbed because of the Rohingya influx. This is resulting in the chaotic conditions in the society which are not letting the legitimate citizens of India to achieve mental peace and grow themselves from inside which is very important to strengthen the character strengths within ourselves. The current paper explains these issues in detail to generate a deep insight among the Indian citizens and to help Government of India in making decisions on this matter.
Keywords: Rohingya; Indians.